Pemanfaatan Limbah Kayu Jati pada Pembuatan Produk Coffee Table Multifungsi - Agung Ari Purwanto; Saor Marakup Simangunsong (Universitas Medan Area, 2026)
This multifunctional coffee table is designed to optimize furniture functionality by utilizing teak wood offcuts from CV. ABC as the primary material. The product, measuring 1120 × 530 × 375 mm, is manufactured through stages of observation, design development, material sorting, component fabrication, assembly, adjustment, and finishing. The frame and apron structure are constructed using a brick-pattern lamination technique, bonded with PVAC adhesive and compressed with a hydraulic press. The tabletop is crafted with a blooming-flower pattern using a radial arm saw and PVAC adhesive. The finishing process applies a rustic old teak style with a water-based coating. The product features an additional sliding drawer integrated into the tabletop, aligning with modern furniture trends emphasizing space efficiency. Based on the bill of materials, the manufacturing process requires 0.1402 m³ of teak wood offcuts.